2021
DOI: 10.1016/j.ekir.2020.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of COVID-19 and Kidney Transplant Recipients, the South West London Kidney Transplant Network Experience

Abstract: Introduction There is paucity of literature comparing outcomes of kidney transplant patients with Covid-19 to that of dialysis and waitlisted patients. This report describes our data, provides comparative analysis, together with meta-analysis of published studies and describes our protocols to restart the transplant programme. Methods Data were analysed on kidney transplant, dialysis and waitlisted patients tested positive for SARS-CoV-2 (naso-pharyngeal swab PCR) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
(80 reference statements)
1
24
0
Order By: Relevance
“…In other studies as well, stopping the anti‐proliferative has been the predominant immunosuppression modification strategy used in management of the transplant recipients with COVID‐19 while the calcineurin inhibitor (CNI) has been stopped in few severe cases. 6 , 22 , 27 , 28 Acute kidney injury was seen in 29.3% of the cases in the present study. Acute kidney injury has been reported to occur in 28%–77% of renal transplant patients with COVID‐19 infection in various studies.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In other studies as well, stopping the anti‐proliferative has been the predominant immunosuppression modification strategy used in management of the transplant recipients with COVID‐19 while the calcineurin inhibitor (CNI) has been stopped in few severe cases. 6 , 22 , 27 , 28 Acute kidney injury was seen in 29.3% of the cases in the present study. Acute kidney injury has been reported to occur in 28%–77% of renal transplant patients with COVID‐19 infection in various studies.…”
Section: Discussionsupporting
confidence: 50%
“…In a meta‐analysis by Phanish et al., a pooled case fatality ratio of 24% was seen. 22 In a regionwide registry study by Meester et al., the crude cumulative mortality rate was 14% in kidney transplant recipients. 3 The COVID‐19 related mortality was 26.8% in the Spanish Society of Nephrology registry data.…”
Section: Discussionmentioning
confidence: 97%
“…allowing a broad-ranging overview and risk assessment for SARS-CoV-2-infected SOT recipients, which may help with addressing the many unanswered key questions urgently arising in this context [6] . Thus, we performed a structured literature review, providing an overview that compiles all relevant scientific literature from January 1 until December 31, 2020 to produce a current synoptic assessment of mortality and clinical outcomes subsequent to infection and COVID-19 in SOT recipients as well as a comprehensive summary of the relevant scientific literature that even a multitude of preceding systematic reviews fall short to provide so far [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…12 A meta-analysis of 16 studies and 871 hospitalized kidney transplant patients with COVID-19 reported a pooled case fatality rate of 24%. 13 Additional similar retrospective studies conducted in Europe, Turkey, and the United States also showed similar increased risk of mortality due to COVID-19 with decreasing renal function, kidney failure, and transplantation. 2,3,9,14,15…”
Section: Does Adpkd Affect My Likelihood Of Hospitalization Need For Dialysis or Mortality If I Develop Covid-19?mentioning
confidence: 71%